On the quality variation impact of returns in remanufacturing - Korugan, Aybek; Dingeç, Kemal Dinçer; Önen, Tolga; Ateş, Nüfer Yasin (Computers & industrial engineering, 2013)
► A two-class production system processing new and used parts is considered. ► Used parts are processed faster but also cause more frequent quality failures. ► The nonconforming production of a machine is modeled with a quality failure state. ► The two-machine two-class production system with a common buffer is analyzed. ► Efficient quality inspection increases effective throughput of remanufacturing. This study considers a two-class production system that is subject to operational and quality failures. A generalized example for such systems is the remanufacturing processes where new and used parts are handled by the same machines. Here the impurities of used parts bring additional load to machines that are shared by new and used parts. In order to analyze the process first the single machine operation is modeled as a Continuous Time Markov Chain. Then based on the single machine model, a model for a two-machine-one-buffer-system is constructed. Here in order to attain computational tractability for systems with larger buffers state aggregation and randomized part type sequencing is considered for both machines. Then using this model the impact of the remanufacturing ratio on the effective throughput rate of the system is numerically analyzed.